Pola Subkontrak Kopi Luwak Satria Agrowisata di Desa Manukaya, Kecamatan Tampak Siring, Kabupaten Gianyar - MADE RISKI DWI SAPUTRA; RATNA KOMALA DEWI; NI LUH PRIMA KEMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Subcontracting Patterns Luwak Coffee Satria Agrowisatain Manukaya Village, Tampak Siring District,Gianyar RegencyGianyar Regency is a tourist area, so a lot of tourists who visit. The number oftravelers and tourists who visit both foreign and locally caused the opening ofbusiness opportunities that can be cultivated. Agrowisata Luwak coffee is one ofthe many businesses that are developing in the Manukaya Village, Tampak SiringDistrict, Gianyar Regency. Luwak coffee is the most expensive coffee at the currentprice, which is why many businesses are choosing to develop this business. Thehigh market demand for coffee, causing a partnership between activists civet with acoffee company to meet the market demand. This study is to determine thefollowing matters : (1) The partnership pattern that occurs between SatriaAgrowisata with activists civet; (2) The rights and obligations Satria Agrowisatawith activists civet; (3) The efficiency of the partnership between for either; (4) Theobstacles faced by the partnership. The results showed that; (1) The Partnershipadopted by Satria Agrowisata with activists civet is a partnership Subcontract; (2)The rights and obligations of both parties must be adhered to in accordance with theagreement that has been agreed; (3) The partnership between Satria Agrowisatawith activists civet is already efficient; (4) Constraints faced Satria Agrowisata inthis partnership is the quality of the coffee produced by activists civet poorly andfraud by breeders civet, while the constraints faced by activists civet is late paymentby Satria Agrowisata and delays in raw material prices.